PENGARUH PREMI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DI PT. BRI LIFE CABANG JAMBI - Emi Eriyani; Sucipto Sucipto; Agustina Mutia (CV. Aksara Global Akademia, 2024)
The purpose of this study was to determine the influence and how much the premium and service quality have on customer satisfaction at pt. Bri life Jambi branch. This research uses a quantitative approach with primary data collection techniques in the form of a questionnaire of 48 respondents. It can be concluded that the variable premium and service quality have a significant effect on customer satisfaction. The results showed that the calculated t value for the premium variable (Xi) was 2.589 with a significance level of 0.013 because t calculated was greater than t table (2.589 <0.05), so it could be concluded that Ho was rejected and Ha was accepted which stated that there was premium significantly positive effect on customer satisfaction Bank BRI Life